Interbehavioral survey about learning by observation in didactic interactions of illustration and feedback - Galindo-Rodríguez, Luis (2017)
In accordance with the principles of the interbehavioral model of didactic performance and the researches carried out in the area of learning by observation, the objective of the following study was to evaluate the effects of the observation of didactic interactions of illustration and feedback on effective performance in a second-order matching-to-sample task with methodological terms of research in psychology as instances. Twenty university students participated, they were assigned randomly in a trial in three experimental groups and a control group. The experimental design was of A-B-A type, with an initial test, training and a final test. The experimental groups were distinguished by the type of observational training which received: illustration, feedback and illustration-feedback. The results indicate that this latter was the most effective according to the average of attempts made to respond to the reagent of the training, as well, as of the increase in the performance of the participants between both tests. These results are discussed in terms of: a) characteristics of the didactic interactions of illustration and feedback, and b) the importance of the linguistic regulation in learning by observation in real educational situations.